A comprehensive assessment of energy storage options for green hydrogen - Karayel, G. Kubilay; Javani, Nader; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
The current study investigates suitable hydrogen storage technologies for hydrogen produced by renewable energy resources in a green manner. Type-I, III, and IV high-pressure tanks, adsorbent storage, metal hydride storage and chemical storage options are investigated and compared based on their hydrogen storage capacities, costs, masses and greenhouse gas (GHG) emissions. The results of this study show that in a Type-IV hydrogen storage tank (i.e., composite material tank of carbon fiber with thermoplastic polymer liners), increasing the tank pressure from 100 bar to 800 bar increases the hydrogen holding capacity by 457.7%. Regarding the environmental impact, the lowest GHG emissions appear to be the lowest for liquid hydrogen storage with an average of 3.5 CO2eq/kg-H2 while the respective emissions become the highest in metal hydride storage tanks as 113.6 CO2eq/kg-H2. Furthermore, hydrogen storage capacity for Type-IV tanks varies from 1.94 kg at 100 bar to 15.69 kg at 1500 bar in a 250 L tank. In chemical hydride storage tanks, the stored H2 mass will be 40.75 kg for 100 L, 128.39 kg for 200 L, 216.03 kg for 300 L, 303.67 kg for 400 L, 391.31 kg for 500 L and 478.96 kg for 600 L, respectively. Moreover, hydrogen storage, distribution and dispensing are considered critically important in hydrogen logistics and the results of this study will help better guide policymakers to establish effective policies and increase renewable energy penetration in the energy market.
Keywords: Hydrogen storage; Metal hydride storage; Liquid hydrogen storage; Cost assessment; GHG emissions; Compressed storage; Green hydrogen; SYSTEMS; GAS; Thermodynamics; Energy & Fuels; Mechanics